LncRNA PVT1 Promotes Hypoxia-Induced Cardiomyocyte Injury by Inhibiting miR-214-3p - Chuanliang Liu (Hindawi Limited, 2021)
Objective. To explore the effect and related mechanism of LncRNA PVT1 on hypoxia-induced cardiomyocyte injury. Methods. PVT1RNA and miR-214-3p levels were detected by quantitative real-time polymerase chain reaction (qRT-PCR). Cell vitality and apoptosis were, respectively, evaluated by Cell Counting Kit-8 (CCK-8) and flow cytometry analysis. Starbase and Dual luciferase reporter (DLR) gene assay was employed to validate the interaction between miR-214-3p and PVT1. Results. PVT1 was statistically upregulated, and miR-214-3p was statistically downregulated in hypoxia-induced H9c2 cells. The survival rate of H9c2 cells induced by hypoxia decreased statistically, while the apoptosis rate increased statistically (P<0.05). PVT1 knockdown upregulated the hypoxia-induced H9c2 cell viability and inhibited apoptosis. DLR assay verified the targeting relationship between PVT1 and miR-214-3p. In addition, miR-214-3p inhibitors reversed the viability of H9c2 cells with PVT1 knockout and promoted apoptosis. Conclusion. Silencing PVT1 can enhance the hypoxia-induced H9c2 cell viability and inhibit apoptosis, providing a potential target for the treatment of cardiovascular diseases.